2015
DOI: 10.4103/0970-1591.152813
|View full text |Cite
|
Sign up to set email alerts
|

Diuresis and inversion therapy to improve clearance of lower caliceal stones after shock wave lithotripsy: A prospective, randomized, controlled, clinical study

Abstract: Objective:To improve the clearance of lower caliceal stones (LCSs) after shock wave lithotripsy (SWL) using a combination of intra-operative forced diuresis and inversion therapy.Materials and Methods:One hundred and fifty-seven consecutive patients with symptomatic, single LCSs of 5–20 mm size were prospectively randomized into two groups. The first (study group, SG) underwent SWL at the time of the maximum diuresis with the patient in the Trendelenburg position with an angle of 30 degree, while the second gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
(57 reference statements)
1
14
0
Order By: Relevance
“… 13 Thus, we evaluated the complications in the remaining five studies. 9 12 , 14 No complications were observed in the Azm and Higazy 9 and Zomorrodi et al. 10 studies, whereas the remaining three studies reported complications after SWL treatment to remove RS.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“… 13 Thus, we evaluated the complications in the remaining five studies. 9 12 , 14 No complications were observed in the Azm and Higazy 9 and Zomorrodi et al. 10 studies, whereas the remaining three studies reported complications after SWL treatment to remove RS.…”
Section: Resultsmentioning
confidence: 93%
“…Finally, we included six RCTs that examined the synergistic action of SWL and furosemide against the actions of SWL alone. 9 14 A flowchart of our inclusion/exclusion process is presented in Figure 1 , and the demographics of the six eligible articles are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the inclusion and exclusion criteria, 6 RCTs [10][11][12][13][14][15] involving 1344 patients were included in the analysis. Table 1 shows the characteristics of the individual RCTs.…”
Section: Characteristics Of Individual Studiesmentioning
confidence: 99%
“…Auxiliary treatment post ESWL Ahmed et al17 defined stone free as no visible stone or residual fragment < 4 mm on x-ray film KUB or ultrasound, and Elkholy et al…”
mentioning
confidence: 99%